Response of the Injured Tendon to Growth Factors in the Presence or Absence of the Paratenon. Issue 2 (February 2019) - Müller, Sebastian A.; Quirk, Nicholas P.; Müller-Lebschi, Julia A.; Heisterbach, Patricia E.; Dürselen, Lutz; Majewski, Martin; Evans, Christopher H.
Background: The paratenon is important for Achilles tendon healing. There is much interest in the use of exogenous growth factors (GFs) as potential agents for accelerating the healing of damaged Achilles tendons. Purpose/Hypothesis: The present study used a rat model to study the responses of the injured Achilles tendon to GFs in the presence or absence of the paratenon. The hypothesis was that responses of the injured tendon to GFs would be lower in the absence of a paratenon. Study Design: Controlled laboratory study. Methods: A 4-mm defect was created in the right Achilles tendon of 60 skeletally mature rats, which were treated with a validated combination of GFs (bFGF, BMP-12, and TGF-β1). Animals were randomly assigned to the intact paratenon (IP) group or resected paratenon (RP) group. Healing was studied anatomically, mechanically, and histologically after 1, 2, and 4 weeks. Results: IP tendons showed improved healing compared with RP tendons. IP tendons were significantly stronger (32.2 N and 48.9 N, respectively) than RP tendons (20.1 N and 31.1 N, respectively) after 1 and 2 weeks. IP tendons did not elongate as much as RP tendons and had greater cross-sectional areas (18.0 mm 2, 14.4 mm 2, and 16.4 mm 2, respectively) after 1, 2, and 4 weeks compared with RP tendons (10.5 mm 2, 8.4 mm 2, and 11.9 mm 2, respectively). On histology, earlier collagen deposition and parallel orientation of fibrils were found for IP tendons. Conclusion: The paratenon is essential for efficient Achilles tendon healing. Healing with GFs in this Achilles tendon defect model was superior in the presence of the paratenon. Clinical Relevance: Biological approaches to tendon engineering using GFs are in vogue and have been shown to improve healing of the rat Achilles tendon, most likely by inducing progenitor cells located within the paratenon. Clinically, resection or incision of the paratenon has been proposed for wound closure. Our data demonstrate the fundamental importance of the paratenon, which therefore should be preserved during Achilles tendon repair, especially if augmented with products such as platelet-rich plasma or autologous conditioned serum that are rich in GFs.